A Long Way to Have Come and Still to Go. - Cerf, Vinton G. (Communications of the ACM, 2015)
The author considers the historical development of computer programming. He observes that in 1953 programming a computer introduced by International Business Machines was considerably more advanced than programming as depicted that year in the novel "Starman Jones" by Robert Heinlein. In 2014 he says programming technology needs further development before it will be possible to perform a high level of computer programming orally.